Incidence of Candida species colonization in neonatal intensive care unit at Riyadh Hospital, Saudi Arabia (Medical Journal of Indonesia, 2016)
Background: Candida species are important hospital-acquired pathogens in infants admitted to the neonatal intensive care unit (NICU). This study was performed in the NICU of Saudi Arabian Hospital, Riyadh region, KSA to analyze patterns of neonatal Candida colonization as well as to determine the potential risk factors. Methods: Weekly surveillance fungal cultures of anal area, oral cavity, umbilicus and ear canal of neonates were performed from birth until their discharge from the hospital. Colonization was analyzed for timing, site, species, birth weight and gestational age. Potential environmental reservoirs and hands of health care workers (HCWs) were also cultured monthly for fungi. Antifungal susceptibility of the identified isolates was also determined. Results: One hundred subjects have been recruited in this study. The overall colonization rate was 51%. Early colonization was found in 27 (27%) neonates whereas 24 (24%) neonates were lately colonized during their stay in NICU. Colonization was more in preterm neonates than in full and post term. Perianal area and oral cavity were the most frequent colonized sites. C. albicans was the main spp. (58.8%) isolated from the neonates followed by C. tropicalis (17.6%), C. glabrata (15.6%), and C. krusei (2%). Of the 51 isolated Candida spp., 68.6% were sensitive to fluconazole, 80% to itraconazole and 64.7% to ketoconazole, while only 33% were sensitive to amphotericin B. Conclusion: Candida has emerged as a common cause of infections in infants admitted to NICU, and C. albicans is the most commonly isolated candidal species. Neonatal infections caused by non- albicans species occur at a later age during their stay in NICU.